Financing Business Innovation : Review of External Sources of Funding for Innovative Businesses and Public Policies to Support Them - World Bank Group (World Bank, Washington, DC, 2015)
Innovation is the main driver of long-term economic growth. The accumulation of capital, whether in the form of physical assets such as plants and equipment, or through better human capital, cannot indefinitely sustain growth unless new products, services, processes, and/or business models are developed and implemented. This paper describes the actors involved and the types of funding available at different stages of the innovation process, the rationales for public intervention, and the advantages and disadvantages of some of the most commonly used policy instruments. Innovation activities are more difficult to finance than other types of investment for several reasons. Innovation produces an intangible asset that does not typically constitute accepted collateral to obtain external funding. Also, the technological and market uncertainty of innovation activities makes the returns to investment highly uncertain, creating significant problems for the standard risk adjustment methods used by providers of funds. This paper uses a streamlined version of an innovation process with three stages to categorize the different sources of finance available; in reality, considerable crossover takes places among instruments because innovation processes are not discrete.